A novel body circumferences-based estimation of percentage body fat. Issue 6 (19th March 2018) - Lahav, Yair; Epstein, Yoram; Kedem, Ron; Schermann, Haggai
Abstract: Anthropometric measures of body composition are often used for rapid and cost-effective estimation of percentage body fat (%BF) in field research, serial measurements and screening. Our aim was to develop a validated estimate of %BF for the general population, based on simple body circumferences measures. The study cohort consisted of two consecutive samples of health club members, designated as 'development' ( n 476, 61 % men, 39 % women) and 'validation' ( n 224, 50 % men, 50 % women) groups. All subjects underwent anthropometric measurements as part of their registration to a health club. Dual-energy X-ray absorptiometry (DEXA) scan was used as the 'gold standard' estimate of %BF. Linear regressions where used to construct the predictive equation (%BFcal ). Bland–Altman statistics, Lin concordance coefficients and percentage of subjects falling within 5 % of %BF estimate by DEXA were used to evaluate accuracy and precision of the equation. The variance inflation factor was used to check multicollinearity. Two distinct equations were developed for men and women: %BFcal (men)=10·1−0·239 H +0·8 A −0·5 N ; %BFcal (women)=19·2−0·239 H +0·8 A −0·5 N ( H, height; A, abdomen; N, neck, all in cm). Bland–Altman differences were randomly distributed and showed no fixed bias. Lin concordance coefficients of %BFcal were 0·89 in men and 0·86 in women. About 79·5 % of %BF predictions in both sexes were within ±5 % of the DEXA value. The Durnin–Womersley skinfolds equation was less accurate in our study group for prediction of %BF than %BFcal . We conclude that %BFcal offers the advantage of obtaining a reliable estimate of %BF from simple measurements that require no sophisticated tools and only a minimal prior training and experience.